Is the problem driven iterative adaptation approach (PDIA) a panacea for public financial management reform? Evidence from six African countries - Lawson, Andrew; Harris, Jamelia (World Development Perspectives, 2023)
This article assesses the application of the problem driven iterative adaptation (PDIA) approach to public financial management reform in six African countries. It draws on primary data collected using a mix of interviews, overt participation observations and a short survey. PDIA responds to shortcomings in orthodox approaches to reform and technical assistance in developing countries. It stresses local solutions to local problems, achieved through experimentation and adaptation. The principles of PDIA are appealing, but its empirical assessment is in its infancy. This study aims to fill part of this gap. Findings show that PDIA delivers results in the short-term, particularly in cases where there is an influential authorising agent and dedicated team. Progress was less forthcoming for reforms that required high level political buy-in from senior officials. The approach does exceptionally well to develop staff capability, transferable skills, and local empowerment to solve local problems, thus potentially benefitting future reforms.

Navigating adaptive approaches for development programmes - Pett, Jamie (Working Paper, 2020)
This working paper compares six of the most prominent adaptive approaches to emerge over the past two decades. Three come from the world of innovation, largely in the private sector (agile, lean startup and human-centred design), and three from the global development sector (thinking and working politically, forms of adaptive management and problem-driven iterative adaptation). While all of these approaches are valuable when used in the right context, practitioners may be perplexed by the multiplicity of methods and jargon. This paper aims to address some of this confusion by mapping where these approaches have come from and showing how they can be applied across the adaptive programme cycle. Armed with this knowledge, practitioners might experiment with different combinations and sequences of adaptive approaches according to the kind of problem and context faced. In turn, this may help us move beyond a siloed view of approaches linked to innovation, adaptive management or more politically smart ways of working. Key messages: • Adaptive approaches have emerged in several sectors, including software development, product and service design, technology startups and international development. • Adaptive approaches can help practitioners counteract misplaced certainty. By talking to potential users, understanding institutions, interests and ideas and investigating the root causes of a problem, practitioners applying these approaches can illuminate the underlying nature of the problem and context. • Rather than building a whole solution straight away, these approaches commonly encourage practitioners to start small and use structured cycles of testing and learning. There is scope to further consider how different approaches can be better brought together and combined. • Adaptive approaches in development provide a wider range of options for what to create and facilitate – not only products or services, but also forms of collective action. There are also alternative ways to think about scale – considering how others might take up an idea and looking for leverage, rather than quantity.

Lessons for PFM Reform - the PDIA Approach in Africa - Bento, Joana (Public Financial Management Blog - IMF, 2021)
Some important lessons are as follows: First, identifying a policy problem is critical for reforms to get traction both at a political and administrative level. Second, appropriate solutions can emerge from a process of experimentation, iteration, and adaptation. Third, building teams and institutional capabilities is a critical part of solving complex problems in a sustainable way.

Building capability by delivering results: Putting Problem-Driven Iterative Adaptation (PDIA) principles into practice - Andrews, Matt; Pritchett, Lant; Samji, Salimah; Woolcock, Michael (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Adaptive programming in practice: shared lessons from the DFID-funded LASER and SAVI programmes - Derbyshire, Helen; Donovan, Elbereth (Synthesis Paper 3, 2016)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others).
Keywords: IMPORTANT; Practice

The Limits of Institutional Reform in Development: Changing Rules for Realistic Solutions - Andrews, Matt (Cambridge University Press, 2013)
Institutional reforms are common across the globe. Think of efforts to build new governments in Afghanistan and Iraq; or decades worth of interventions intended to improve fiscal management, reduce corruption or introduce efficient public sector service delivery in African countries.These reforms often have limited results, however. They lead to new laws that are not properly implemented, and new organizations that have poor capacities and fail to function as needed. In this book, Matt Andrews explains why reform results are frequently limited and suggests ways to overcome these limits. In the first half of the book, Andrews argues that reforms fail to make governments better when they are introduced as signals to gain short-term support--from donors and others. Reforms as signals introduce unrealistic best practices that do not fit developing country contexts and are not considered relevant by implementing agents. The result is a set of new forms that do not function properly. Andrews uses examples to prove this point, ranging from efforts to introduce fiscal rules in Argentina to reforms aimed at international accounting standard adoption in many African countries, and anti corruption interventions in Malawi and Uganda. In the second half of the book, Andrews notes that there are instances where reforms are not being introduced as signals, and are having more of an impact on government effectiveness. Examples include local government reforms in Rwanda, anti corruption initiatives in Indonesia, and a variety of initiatives ranging from results based management to civil service modernization and internal control regime adoption in governments like Kenya, Kosovo and Afghanistan. Andrews uses these examples to discuss ways in which reforms can actually provide realistic solutions to governance challenges in developing countries. Lessons from these experiences suggest that reform limits can be overcome by focusing interventions on problem solving, and promoting incremental and localized processes to find solutions, involving multiple agents who can authorize and implement reforms.

Where have we got to on adaptive learning, thinking and working politically, doing development differently etc? Getting beyond the People’s Front of Judea - Algoso, Dave; Hudson, Alan (From Poverty to Power, 2016)
Dave Algoso and Alan Hudson at Global Integrity compare and contrast 9 different initiatives that are all heading in roughly the right direction in aid reform
Keywords: IMPORTANT

PFM Reform Through PDIA: What Works and When it Works - Harris, Jamelia; Lawson, Andrew (Public Financial Management Blog - IMF, 2022)

PDIA Notes 2: Learning to Learn - Samji, Salimah (Building State Capability, 2016)
written by Peter Harrington After over two years of working with the government of Albania, and as we embark on a new project to work with the government of Sri Lanka, we at the Building State Capa…

It's All About MeE: Using Structured Experiential Learning (“e”) to Crawl the Design Space - Pritchett, Lant; Samji, Salimah; Hammer, Jeffrey (Working Paper 322, 2013)
This paper argues that within-project variations in design can serve as their own counterfactual, reducing the incremental cost of evaluation and increasing the direct usefulness of evaluation to implementing agencies. It suggests combining monitoring (‘M’), structured experiential learning (‘e’), and evaluation (‘E’) so as to facilitate innovation and organisational capability building while also providing accountability …

Scenario-based strategizing: Advancing the applicability in strategists' teams - Lehr, Thomas; Lorenz, Ullrich; Willert, Markus; Rohrbeck, René (Technological Forecasting and Social Change, 2017)
For over 40years, scenarios have been promoted as a key technique for forming strategies in uncertain environments. However, many challenges remain. In this article, we discuss a novel approach designed to increase the applicability of scenario-based strategizing in top management teams. Drawing on behavioural strategy as a theoretical lens, we design a yardstick to study the impact of scenario-based strategizing. We then describe our approach, which includes developing scenarios and alternative strategies separately and supporting the strategy selection through an integrated assessment of the goal-based efficacy and robustness. To facilitate the collaborative strategizing in teams, we propose a matrix with robustness and efficacy as the two axes, which we call the Parmenides Matrix. We assess the impact of the novel approach by applying it in two cases, at a governmental agency (German Environmental Ministry) and a firm affected by disruptive change (Bosch, leading global supplier of technology and solutions).
Keywords: Behavioural strategy; Scenario-based strategizing; Scenarios; Strategic foresight; Uncertainty

Thinking and Working Politically – Are We Seeing the Emergence of a Second Orthodoxy? - Teskey, Graham (Governance Working Paper 1, 2017)
There now is a persuasive volume of evidence that demonstrates that capacity and technical knowledge alone are insufficient to change deeply entrenched political interests and bureaucratic norms. These critiques demonstrate that an understanding of power asymmetries is frequently the critical missing ingredient in project design and implementation. Many eminent thinkers have looked at the difference between success and failure in development, and all point to the primacy of domestic politics. This point has not been lost on development agencies and some have tried to provoke greater attention to the role that politics plays. However, this recognition is yet to pass into the mainstream of development practice. Despite the slow but sure accretion of this knowledge the international community seems to be wedded to doing development traditionally. The purpose of this paper is to consider the extent to which a ‘second orthodoxy’ is slowly emerging which can stand alongside, and in some cases may supplant, the ‘first orthodoxy’ of the traditional project framework. Care has to be taken in making this argument, as there is certainly no consensus within the development community on its importance, and even among advocates, there are slightly differing interpretations of what this second orthodoxy looks like. Further, it is not absolutely clear that the two orthodoxies can co-exist. The paper does not call for any ‘paradigm shift’ in how development practitioners conceptualise programs and projects, nor does it demand that the project framework be scrapped; the former would be impossible and the latter undesirable. Equally readers will find no claims that Doing Development Differently or ‘Thinking and Working Politically’ will always and everywhere guarantee better development outcomes. Rather, the paper seeks to summarise how the two orthodoxies differ, where the second orthodoxy now stands, and propose how it can be taken forward in practical terms.

Monday morning in Kigali: what do you do when you get off the plane? Practical guidance for PDIA practitioners - LASER (Synthesis Paper, 1, 2016)
In order to help enhance the effectiveness of donors and development practitioners on the ground, LASER has produced a range of practical guidance and tools. These are primarily intended for the international development community engaged in designing and implementing investment climate programmes, though can also be used more widely by other stakeholders across sectors. General guidance and tools: Monday morning in Kigali January 2016 - what do you do when you get off the plane? Practical guidance for PDIA practitioners
Keywords: IMPORTANT; Practice